The role of competition, innovation, and regulation on financial intermediary risk. Issue 12 (24th September 2019) - Schaffer, Marc
Abstract : Purpose: This macroeconomic analysis chronicles the risk behavior of market-based financial intermediaries and traditional depository institutions from 1980 to 2010 and assesses the role that competition, financial innovation and regulation played in their evolving risk behaviors. The paper aims to discuss these issues. Design/methodology/approach: Using a two-part CAPM framework in line with Campbell et al. (2001), risk measures are constructed through the decomposition of industry-level risk and firm-level idiosyncratic risk. These constructed measures are used in a VAR model with a historical decomposition approach to assess the impact of the three factors on the relative risk behavior of these firms. Findings: The results indicate that the market-based and traditional intermediaries exhibited a period of diverging relative average firm-level risk behavior followed by a period of converging risk behavior. Using the derived firm-level risk measures, the impact of competition, financial innovation and regulatory changes on explaining these changing risk behaviors is explored. The results suggest that regulatory changes (i.e. deregulation) can best explain the relative risk behavior over the divergence period through late 1999 relative to the other two variables. The period from November 1999 through the financial crisis marks the converging risk behaviors across these intermediaries. Over this period, the changing nature of competition played the most important role in driving these behaviors. Originality/value: The key contribution of this analysis highlights the evolutionary changes in the risk behaviors of market-based and traditional financial intermediaries and the factors driving both their diverging and converging nature over time.